A Management System to Develop Occupational Health & Safety in Ground Control Operations of Underground Mines - Kazem Oraee (International Conference on Ground Control in Mining, 2012)
Falls of ground have historically been the main cause for fatalities in underground mines. Although recent advances in technology have reduced the number of such accidents, when failures occur they usually result in severe consequences. Risks of rock falls, use of heavy machinery and electrical apparatus, entry to confined spaces, working in noisy and dusty environments, and working on unstable platforms are some of the hazards in ground control operations. Managing these risks requires a management regime involving strict adherence to operational codes of practice and an enshrined culture of safety. These should be subsequently reinforced through active participation of management, systematic training, and stringent internal and third party auditing. Accident reports show that the major contributing factor in most rock fall accidents is the failure to adequately manage known risks due to the lack of a systematic process. OHSAS 18001 (Occupational Health and Safety Assessment Series) is an international occupational health and safety management standard specification to develop occupational health and safety at the workplace. This standard is intended to help mine operators control occupational health and safety risks. Addressing the requirements of OHSAS 18001 can be a complex and demanding task. A comprehensive guide for efficient and accurate implementation of this standard is provided in this paper. The discipline can be used to establish an accountable management system foreground control activities in underground coal mines. The paper also provides guidelines for preparing necessary documents, devising safety policies, procedures, performing risk assessment, and handling instructions. Finally, the paper concludes by providing a sound analytical basis in terms of the creation of a robust safety management system foreground control operations in underground mines. Full benefits of implementing an effective and systematic operational health and safety management system are illustrated. The procedure adopted and prescribed in this paper can be used in all underground coal mines where lack of appropriate ground control practices can create deficiencies in both safety and productivity.